Dental Fear of Children and Its Relationship with Caries Experience: Dental Fear and Dental Caries - Varmazyar, Afshin; Taram, Saman; Razavi Rohani, Zahra (Journal of Dental School, 2021)
Objectives The aim of this study was to assess dental fear and its relationship with demographic information and dental caries experience in 6 to 12-year-old children residing in Urmia city in 2020. Methods In this cross-sectional study, 185 children referred to the Pediatrics Department of Alborz Dental Clinic were included. The Children’s Fear Survey Schedule-Dental Subscale (CFSS-DS) was used to evaluate dental fear experience of children. Demographic characteristics including sex, gender, parents’ educational level and birth order were also recorded. Intraoral examination was performed by a pedodontist, and dental caries experience was recorded based on the DMFT index. The data were analyzed by the Chi-square and logistic regression test using SPSS version 16.0. Results Of 185 children, 83 were boys and 102 were girls; 136 participants had no dental fear while 49 had dental fear. The prevalence of dental fear was 26.48%. There were significant correlations between children’s age (P=0.006) and birth order (P= 0.007) with their dental fear. But there was no significant correlation between gender or father’s educational level with dental fear experience (P=0.812), or dmft/DMFT index (P=0.128). Also, dental injection (71%) and drilling (49%) followed by the noise of drilling (45%) caused the highest mean fear among children. Conclusion The findings of the present study suggest that dental fear experience is probably not correlated with caries experience in 6 to 12-year-old children.